History of the Development of Home Education in The Countries of The World - Nurmatova Shakhnoza Shavkatbekovna (Euro Asian Journal Publishing, 2023)
The article will talk about the need to develop home education in the conditions of an innovative cluster of teacher education the history of home education in developed countries
Keywords: Home education; Development; Law